1992
DOI: 10.1016/0741-5214(92)90003-q
|View full text |Cite
|
Sign up to set email alerts
|

Primary venous leiomyosarcoma: A rare but lethal disease

Abstract: Primary venous leiomyosarcoma is rare, only 197 patients have been reported. To examine progress in diagnosis, treatment, and clinical outcome, we retrospectively reviewed data of 13 patients, 12 women and one man (mean age, 55 years; range, 19 to 75 years), who in the last 35 years underwent surgical treatment for primary venous leiomyosarcoma at our institution. The tumor arose from the inferior vena cava in eight, iliac vein in two, ovarian vein in one, and greater saphenous vein in two patients. Primary ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
157
0
9

Year Published

1995
1995
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 204 publications
(169 citation statements)
references
References 18 publications
3
157
0
9
Order By: Relevance
“…Vascular LMS is a rare tumor origin the media of vessel walls, low extremities veins are the most commonly veins affected, furthermore, the popliteal and tibial veins even less frequently, some few cases have been published [1,[4][5][6] . The diagnostic of leiomyosarcoma, it must first be distinguished from other types of tumors, that differentiate these tumors from other soft tissue sarcomas it's not easy to do, a good histological and immunohistochemical study using markers are useful for the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Vascular LMS is a rare tumor origin the media of vessel walls, low extremities veins are the most commonly veins affected, furthermore, the popliteal and tibial veins even less frequently, some few cases have been published [1,[4][5][6] . The diagnostic of leiomyosarcoma, it must first be distinguished from other types of tumors, that differentiate these tumors from other soft tissue sarcomas it's not easy to do, a good histological and immunohistochemical study using markers are useful for the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them were high grade histologically, and 7/16 patients (44%) at the time of diagnosis. Dzsinich et al (1992) [5] reported on 13 cases of vascular LMS, which 8/13 arose from the inferior cava vein 2/13 from the iliac vein, and 2/13 cases from the saphenous vein. Svarvar et al (2007) [6] reported on 225 patients with LMS of all types from the Scandinavian Sarcoma Group with a cumulative survival of 49% at 10 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations